Factors influencing electronic health record adoption by physicians: A multilevel analysis. Issue 3 (June 2016) - Gagnon, Marie-Pierre; Simonyan, David; Ghandour, El Kebir; Godin, Gaston; Labrecque, Michel; Ouimet, Mathieu; Rousseau, Michel
Highlights: We aimed to assess the influence of organization-level characteristics on physician intention to use EHR. We used a multilevel regression model to explore organization-level and individual-level effects. In Quebec, organization-level characteristics have no significant impact on EHR adoption by physicians. Strategies are more likely to succeed if targeting individual physicians. Abstract: In Canada, the healthcare system remains paper-laden, and EHR adoption by physicians lags behind many other industrial countries. Recent reviews identified individual and organizational factors as having the most important influence on EHR adoption and proposed taking a multidimensional perspective to study these adoption determinants. However, most studies have focused on physician EHR adoption measured at the individual level. Objectives: First, we used a multilevel regression model to assess whether organizations' characteristics influenced physician behavioral intention to use EHR. Second, we sought to identify individual and organizational factors that explain physician intention. Methods: We conducted a prospective cross-sectional study among physicians in 49 primary healthcare organizations in four regions of the province of Quebec (Canada). We first analyzed relationships between individual and organizational variables and intention. Second, we performed multilevel modeling to explore organizational characteristics' impact on physician intention to use EHR. Results: 278 completed questionnaires were returned from the 31 organizations that had at least 5 participants (response rate: 39.8%). Questionnaires showed satisfactory psychometric properties. The multilevel modeling found no significant overall influence of organizational level on physician intention to use EHR. Second, six of the individual level constructs had a positive and strongly significant impact on physician intention. Conclusion: In the Quebec context, organization-level seems to have no significant impact on EHR adoption by physicians. Hence, particular strategies are more likely to succeed if they target individual physicians rather than organizations.